PENGARUH KACANGAN PENUTUP TANAH Mucuna bracteata TERHADAP BEBERAPA SIFAT FISIK DAN KIMIA TANAH ULTISOL PADA PERKEBUNAN KARET (Hevea brasiliensis) - Sakiah Sakiah; Mariani Sembiring; Tosuko Utomo (Institut Teknologi Sawit Indonesia, 2018)
The objective of this research is to find out the influence of Mucuna bracteata as cover crop on some physical and chemical properties of ultisol at rubber plantation area with immature plant period on flat and slope ultisol area. The research was conducted at Bandar Pinang Estate, PT. Tolan Tiga Indonesia (SIPEF Group), Desa Bandar Pinang, Bintang Bayu Sub-district, Serdang Bedagai District, Sumatera Utara Province from May to August 2016. Soil sampling is distinguished by plant age, topography and the presence of cover crop (Mucuna bracteata). The soil is taken composite by the zigzag method. From each point is taken as much as 1 Kg of soil using a soil drill at a depth of 0-20 cm then mixed well and used as much as 5 Kg. Data processing is done descriptively. The observation parameters were soil texture, bulk density, infiltration, organic matter content, nitrogen content and soil pH. Mucuna bracteata planting was influencing on some physical and chemical properties of ultisol in rubber plantation. The role of Mucuna bracteata to physical properties of ultisol is to fix bulk density in flat area as 9.22% and on slope area as 2.19%. The average infiltration class goes into the quick criteria and the soil texture is sandy loam soil. The role of Mucuna bracteata to chemical properties of ultisol is to increase soil organic matter in flat area as 44.96% and on slope area as 59.15%, increase the soil nitrogen level in the flat area as 57.14% and in the slope area as 91.67%, there was no significant diﬀerence between pH in both flat and slope areas.